Detection of Virulence Factors of Local Isolates of Proteus mirabilis - Ali, Touka H; Jasim, Hameed M (Al-Nahrain Journal of Science, 2018)
A total of eighty five samples were collected from different clinical and food samples includes twenty samples of urine, forty five samples from wounds, and twenty samples of chicken and meat. From the overall samples a total of 146 isolates were obtained, and among the monly fifteen isolates were belong to P. mirabilis according to the results of identification by studying their morphological and cultural characteristics and biochemical tests. Results of identification were confirmed by using Api20E system. Pathogenicity of local isolates of P. mirabilis was examined by detecting several virulence factors includes invasion and adhesion ability and protease production. Results showed that the adhesion of these isolates to uroepithelial was ranged between 30-55 bacterial cell/uroepithelial cell, and number of bacterial cells invade uroepithelial cells was ranged between 1-20 bacterial cell/uroepithelial cell. Furthermore all of the isolates of P.mirabilis were able to produce protease as another virulence factor forpathogenicity. the diameter of zone of hydrolysis on skim milk agar was ranged between 5-14 mm for different isolates. Specific activity of protease produced in culture filtrates of these isolates was ranged between 14.5 and 0.121 U/mg protein. The most virulent isolate was P. mirabilis P15 isolated from urine of urinary tract infection because of its high ability to produce these virulence factors.